Conhecimento dos profissionais de saúde da atenção primária do município de Aracoiaba (CE) sobre tuberculose - Sousa, Fabio Freitas de (2016)
This study aimed at analyzing the health-care professionals’ knowledge on tuberculosis treatment, who work with primary health care (PHC) in the city of Aracoiaba, Ce. It is a cross-sectional study performed in the period from February to June 2016, with 96 health care professionals, including 11 nurses, 10 doctors, 16 nursing auxiliaries and nursing technicians, and 59 community health agents. Therefore, information about sociodemographic aspects and academic qualification were collected, furthermore the professional’s knowledge about transmission, diagnose, treatment, cure, and control over tuberculosis was evaluated. The application of the research instrument was performed at basic care units in the city. Thus, data were stored in the database structured in the Excel 2013 program, and thereafter analyzed (descriptive analysis). In order to evaluate the existence of statistically significant differences it was applied a Chi-square or Fisher’s exact test (p<0,05, SPSS 17.0). The results indicated that most patients of all categories were female (87.5%) on average age of 40.2 years old. Nurses, doctors, nursing auxiliaries and nursing technicians had less than five years of experience at APS, but more than ten at ACS. The most part of nurses and doctors had post-graduation courses, especially in Family Health. However, the majority of the professionals never took training course on tuberculosis. Regarding transmission of TB, most of them did not know much about laryngeal TB transmission, and they were not able to identify neoplasias and diabetes mellitus as risk factors for TB transmission as well. In considering diagnosis, most of the participants pointed out the main signs of the disease, they were not able to classify a respiratory symptomatic patient, and TB contacts, though. Nurses and doctors showed difficulty in pointing out the exams that should be requested for contacts, and also regarding the necessity of requesting culture and sensitivity test. More than 70% of nurses and doctors correctly recognized the drugs used in the treatment of TB, which contrasted with nurse auxiliaries and nurse technicians (50%), and CHA (13.6%). All participants showed difficulties concerning the right time for a patient stops transmitting the disease after the beginning of treatment, but they had a good performance at Directly Observed Therapy, Short-course. Concerning criteria of cure for patients with TB, only four doctors and two nurses answered correctly. All categories were successful on actions of control of TB, except for the prescription of the BCG vaccination for contacts of people with TB. Thereby, the professionals of PHC were successful in some of the evaluated parameters, but they also showed deficiency on elementary and essential knowledge for clinical management and patient care which are fundamental for therapeutic success. Therefore, conducting educative interventions are crucial in order to provide quality assistance for citizens of the city of Aracoiaba, and meeting the objectives of programa nacional de controle da tuberculose.